2018
DOI: 10.3389/fphys.2018.01561
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Coenzyme Q10 in the Pathogenesis of Preeclampsia

Abstract: Hypertensive disorders during pregnancy constitute one of the main causes of maternal and perinatal morbidity and mortality across the world and particularly in developing countries such as Ecuador. However, despite its impact on public health, the primary pathophysiological processes involved are yet to be elucidated. It has been proposed, among other theories, that an abnormal placentation may induce an endothelial dysfunction, which is ultimately responsible for the final clinical manifestations. Mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Studies on placentas exposed to higher levels of air pollution show placental mitochondrial DNA methylation (70) and decreased placental mitochondrial DNA content (71). Such mitochondrial dysfunction has been proposed to be one of the mechanisms contributing to the dysfunctional placenta in PE (72).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on placentas exposed to higher levels of air pollution show placental mitochondrial DNA methylation (70) and decreased placental mitochondrial DNA content (71). Such mitochondrial dysfunction has been proposed to be one of the mechanisms contributing to the dysfunctional placenta in PE (72).…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme Q10 is a form of fat-soluble ubiquinone in human and is mainly located in the mitochondria. 10 Given the crucial role of coenzyme Q10 in the MRC and other mitochondrial functions, the abnormal absence of coenzyme Q10 leads to various clinical defects including hypertension, metabolic diseases, and atherosclerosis. 21,22 The therapeutic potential of coenzyme Q10 has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the correlation between the decreased coenzyme Q10 level in plasma and the incidence of preeclampsia. 10 And coenzyme Q10 has been reported to attenuate the symptoms of preeclampsia in a rat model. 28 However, the detailed mechanism of coenzyme Q10…”
Section: Discussionmentioning
confidence: 99%
“…The effective function of mitochondria depends on various cofactors, such as L-carnitine, α-lipoic acid, and CoQ10 (Pagano et al, 2014). CoQ10 is particularly interesting because it not only supports the mitochondrial respiratory chain, but also acts as a powerful antioxidant by neutralizing free radicals in various membrane structures (Teran et al, 2018). CoQ10 not only inhibits apoptosis (Chen et al, 2011), but also ferroptosis (Shimada et al, 2016).…”
Section: Coq10 Systemmentioning
confidence: 99%